A comunicação organizacional e as relações de trabalho em cooperativas de economia solidária : a cultura simbólica tecendo a identidade e o imaginário dos cooperativados - Colpo, Caroline Delevati (2012)
This research, undertaken at the Agricultural Cooperative of Production and Commercialization Vida Natural Coopernatural, in Picada Café, called mountain region of Rio Grande do Sul, consists in a study about organizational communication and the working relationships in solidarity economy cooperatives. With a transdisciplinary construction, the main objectives were to discuss solidarity economy cooperatives in the ongoing capitalist process, as well as understanding how the working relationships constitute and are constituted by the organizational communication in the context of solidarity economy cooperatives and comprehending in what ways the myths, rites, heroes and power relationships, while symbolic elements of the organizational communication, interact, alter, interfere and (re)create the identities and the imaginary of the cooperative members. This study was built under the Complexity Paradigm, through the dialog with the Symbolic Interactionism, mainly in attempt of learn/understand the symbolic communication existing/identified in the cooperative and in the statements of the cooperative members. The technics of research are bibliographic, documental, participants observations and in-depth interviews. For reflection / discussion of the issues involved in this work, some theoretical concepts about social economy and solidarity economy, working relationships, organizations, communications, identity and imaginary, organizational communication and symbolic culture through elements of myths, rites, heroes and power relationships were taken into consideration. The observations and interviews allowed some considerations even if temporary, of which emphasize that the dynamics of solidarity economy in the capitalist market and the values that keep the group together are mainly economical. Moreover, the organizational communication constitutes much more the working relationships than they constitute an organizational communication of Coopernatural. By researching aspects of the organizational culture (myths, rites, heroes, and power relationships) through communicative processes between the cooperative members, it is inferred that the commercialization of products is mainly part of the identities, and the solidarity as a part of the imaginary of the cooperative members. In this configuration, further insights for the explanation of communicational phenomena are sought, with eyes focused on the communities and their economic realities in which the constant culture (re)construction alters, interferes and (re)creates the identities and the imaginary of the community-living groups.